1993
DOI: 10.1080/10629369308028814
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dependence of Fish Bioconcentration on n-Octanol/Water Partition Coefficient

Abstract: The log-log relationship between the bioconcentration tendency of organic chemicals in fish and the n -octanol/water partition coefficients breaks down for very hydrophobic compounds. The use of parabolic and bilinear models allows this problem to be overcome. The QSAR equation log BCF = 0.910 log P - 1.975 log (6.8 10(-7) P + 1) - 0.786 (n = 154; r = 0.950; s = 0.347; F = 463.51) was found to be a good predictor of bioconcentration in fish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 23 publications
6
78
1
Order By: Relevance
“…Connell and Hawker (58) reanalyzed published bioconcentration data for fish and proposed a fourth-order polynomial relationship with a maximum wet weight log BCF value of 4.6 for compounds with a log Kow value of 6.7. Related parabolic (second order) and bilinear relationships have been proposed by Bintein et al (59). The apparent BCFs determined for Asellus are in agreement with these curvilinear relationships.…”
Section: Bcf In Relation To Kow the Bcfs Observed For Pahs In A Aqusupporting
confidence: 78%
“…Connell and Hawker (58) reanalyzed published bioconcentration data for fish and proposed a fourth-order polynomial relationship with a maximum wet weight log BCF value of 4.6 for compounds with a log Kow value of 6.7. Related parabolic (second order) and bilinear relationships have been proposed by Bintein et al (59). The apparent BCFs determined for Asellus are in agreement with these curvilinear relationships.…”
Section: Bcf In Relation To Kow the Bcfs Observed For Pahs In A Aqusupporting
confidence: 78%
“…Equation 19 gives such a drop, where the bioconcentration reaches a maximum and then falls above log K ow of 6. Devillers et al (1998) found that the Bintein et al (1993) gives good simulation results and that the model presents a large log K ow domain of application.…”
Section: Empirical Bcf Modelsmentioning
confidence: 98%
“…USEPA (1995aUSEPA ( , 1995c. Devillers et al (1996) studied several published correlations for bioconcentration factor and recommended the equation reported by Bintein et al (1993). This model relates BCF fish (L/kg fish tissue) to K ow , log 0.91× log -1.975 log (6.8 -7 × + 1) -0.786…”
Section: Bioaccumulation In Fishmentioning
confidence: 99%
See 2 more Smart Citations